2019
DOI: 10.1371/journal.pone.0216894
|View full text |Cite
|
Sign up to set email alerts
|

Can we use rapid lifetime determination for fast, fluorescence lifetime based, metabolic imaging? Precision and accuracy of double-exponential decay measurements with low total counts

Abstract: Fluorescence lifetime imaging microscopy (FLIM) can assess cell’s metabolism through the fluorescence of the co-enzymes NADH and FAD, which exhibit a double-exponential decay, with components related to free and protein-bound conditions. In vivo real time clinical imaging applications demand fast acquisition. As photodamage limits excitation power, this is best achieved using wide-field techniques, like time-gated FLIM, and algorithms that require few images to calculate the decay parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Analogous to integral approximation methods in calculus, having more time gates with smaller widths results in higher lifetime accuracy, particularly for fluorophores with short lifetimes or multiexponential decay, while having a longer overall detection time improves accuracy for longer fluorescence lifetimes [ 46 ]. Adding more gates or increasing the detection window size leads to longer acquisition times and lower throughput; however, analysis algorithms [ 21 , 47 ] and even deep learning [ 22 ] have been implemented to maintain accuracy while collecting less images or gates. Similar detectors used for TCSPC can be used in time-gated FLIM, including modified SPAD arrays with gating electronics.…”
Section: High-throughput Flim (Ht-flim)mentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to integral approximation methods in calculus, having more time gates with smaller widths results in higher lifetime accuracy, particularly for fluorophores with short lifetimes or multiexponential decay, while having a longer overall detection time improves accuracy for longer fluorescence lifetimes [ 46 ]. Adding more gates or increasing the detection window size leads to longer acquisition times and lower throughput; however, analysis algorithms [ 21 , 47 ] and even deep learning [ 22 ] have been implemented to maintain accuracy while collecting less images or gates. Similar detectors used for TCSPC can be used in time-gated FLIM, including modified SPAD arrays with gating electronics.…”
Section: High-throughput Flim (Ht-flim)mentioning
confidence: 99%
“…The applications of fluorescence lifetime measurements range significantly. Some examples include separating fluorophores that have similar spectra but different lifetimes [4][5][6][7][8][9][10][11][12][13], exploiting the difference in lifetime of free and bound metabolites for metabolic study and diagnosis [14][15][16][17][18][19][20][21][22][23][24], using FRET to screen for binding or inhibition of exogenous and endogenous molecules of interest [2,5,[25][26][27][28][29][30][31][32][33][34][35], evaluating the conformation and stability of proteins or other molecules in varying environments [31,36], or even using lifetime as an additional parameter in fluorescent inks for anti-counterfeiting [37], though this list is far from exhaustive. New methods and technologies continue to be discovered, further establishing the wide-reaching significance and potential of fluorescence lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…This work has also used Becker & Hickl TCSPC data recording on a Dermainspect MPM in our in vivo real time clinical imaging approach. Others have proposed a wide-field, timegated FLIM approach based on only four images, with high precision being achieved by either a summing of frames or by use of pixel-binning [77]. However, our work here has shown that spatial resolution may be compromised by pixel binning, leading to erroneous results in heterogeneous samples and the summing of frames may also need to be corrected for intravital motion [10].…”
Section: Discussionmentioning
confidence: 89%
“…In such experiments, fast estimation of the lifetime is an important feature. The problem of rapid evaluation of lifetime is important not only for ion traps, but also for luminescence and fluorescence applications [22][23][24], and is also related to the estimation of damping sinusoids and exponential parameters, which has received considerable interest in the signal processing community (see for example [25][26][27] and references therein).…”
Section: Introductionmentioning
confidence: 99%